(–)–Epicatechin combined with 8 weeks of treadmill exercise is associated with increased angiogenic and mitochondrial signaling in mice - Lee, Icksoo; Hüttemann, Maik; Kruger, Adele; Bollig-Fischer, Aliccia; Malek, Moh H. (Frontiers in Pharmacology, 2015)
The purpose of this study was to conduct an 8 week endurance training program with and without (-)-epicatechin treatment and to determine whether there is a possible cumulative effect on protein markers of angiogenesis and mitochondrial biogenesis. Thirty-four 14 month old male mice (C57BL/6N) were randomized into four groups: control (C); (-)-epicatechin only ((-)-Epi); control with endurance training (CE); and (-)-epicatechin with endurance training ((-)-Epi Ex). Mice in the training groups performed treadmill exercise for 8 weeks (5x/week for 60 min/session), whereas mice in the (-)-epicatechin group received 1.0 mg/kg of body mass twice daily during the training period. At 8 weeks, distance ran on the treadmill increased by 46%, 69%, and 84% in the (-)-Epi, CE, and (-)-Epi Ex groups, respectively compared to the control group (p < 0.001 for all comparisons). Furthermore, the ( ) Epi Ex group had significantly higher exercise capacity than the (-)-Epi and CE group. For angiogenic regulators, the (-)-Epi Ex group had significantly higher VEGF-R2 protein expression with a concomitant reduction in TSP-1 protein expression than the exercise group. Interestingly, FoxO1 protein expression was significantly reduced for all three experimental groups compared to the control group. Protein markers such as PGC-1beta and TFAM were significantly higher in the (-)-Epi Ex group compared to the three other groups. These findings suggest that (-)-epicatechin treatment combined with 8 weeks of endurance training provide a cumulative effect on a number of angiogenic and mitochondrial signaling which functionally translates to enhanced exercise tolerance.